Air barriers used for separating smoke free zones in case of fire in tunnel - Krajewski, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The aim of this paper is to take the advantage of CFD application in calculating, optimising, and designing air curtains used to separate smoke free zones in case of fire in tunnel. Air curtains can be a good solution in case when the usage of solid obstructions is not feasible(for example in a big tunnel). A properly designed air curtain produces a pressure drop which prevents transversal flow through the opening. An accurate CFD calculation of an air curtain is challenging because of the high air velocity and relatively thin nozzle. Most air curtains are tested on scaled down models which are difficult to extrapolate. Tests in a real scale model are performed and the tests results are used to verify the chosen turbulence model. The intention of this paper is to present the comparison between the CFD calculations and tests results.